In-situ cracking of oil into gas in reservoirs identified by fluid inclusion analysis: Theoretical model and case study. (January 2023) - Song, Yifan; Chen, Yong; Wang, Miao; Steele-MacInnis, Matthew; Ni, Rui; Zhang, Hui; Fan, Junjia; Ma, Xingzhi; Zhou, Zhenzhu
Abstract: Natural gas formed by cracking of crude oil occurs in many basins globally. One of the key questions about such gas is whether it was produced in-situ—by cracking of crude oil in the reservoir itself—or whether it was generated elsewhere and accumulated in the reservoir subsequently. Fluid inclusions trapped in minerals can provide direct evidence regarding the genesis of natural gas, because these inclusions represent samples of the fluid present at the time of trapping, and/or resulting from subsequent modification of the trapped fluid. Here, we outline some theoretical aspects of the processes of cracking, trapping of fluid inclusions, and potential post-entrapment modifications, that lead to a model for identifying evidence for in-situ cracking of crude oil in reservoirs based on fluid inclusion assemblages (FIAs). This model divides the crude oil cracking process into three main stages, and considers the predicted evolution of fluids and possibility of forming FIAs. In the initial step, before cracking, only liquid oil and aqueous fluid are present in a reservoir, and two endmember types of inclusions may be formed. If cracking of crude oil occurs in the reservoir after these inclusions were trapped, then in-situ cracking of oil within the inclusions gives rise to systematic changes that can be interpreted through the lens of progressive thermal maturation, and hence provide direct evidence for cracking in the reservoir. In the second step, during cracking, the reservoir may host up to four fluid phases (residual oil, aqueous fluid, natural gas, and solid bitumen), and in theory as many as fourteen types fluid inclusions can be trapped; hence, complex FIAs comprising multiple fluid inclusion types can be considered evidence for trapping during in-situ cracking of crude oil in the reservoir. In the third and final step, after complete cracking, liquid oil has been exhausted and only natural gas, solid bitumen and aqueous fluid remain in the reservoir; at this stage, up to six fluid inclusion types can be trapped, which can be indicative of cracking. We applied this model to study the genesis of natural gas in the Sinian Dengying Formation reservoir of the Anyue Gas Field in the Sichuan Basin, southwest China. Six types of hydrocarbon-bearing primary fluid inclusions were observed in fluorite crystals formed during hydrocarbon accumulation. Notably, one type of inclusion showed consistent volumetric phase ratios of solid bitumen plus gas, suggesting that these inclusions originally captured crude oil, which subsequently underwent in-situ cracking in a closed system (within the inclusions) to generate fixed proportions of gas and solid bitumen. These FIAs are consistent with our model and suggest that the fluid inclusions trapped in fluorite can record the in-situ cracking of crude oil in the reservoir, and can therefore be used as direct evidence for the genesis of natural gas. Graphical abstract: Image 1 Highlights: A theoretical model is established for identifying in-situ cracking of oil by fluid inclusion analysis. Multiphase fluids formed by oil cracking can be recorded by fluid inclusions. Gas in Dengying formation of Anyue Gas Field was generated by in-situ cracking of oil.